Personal and Social Development of Children with Mental Impairments with Emotional Disorders - Dini Zatalini (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2022)
This study aims to find out how personal and social development of children with mental impairments. This research is a case study research using qualitative descriptive methods in the elaboration of research results. Then, the data analyzed in this study were sourced from journals, dissertations, and related scientific articles. Based on the research that has been carried out, the results show that there are several causes of emotional and behavioral disorders in children and several classifications such as psychiatric classification, classification according to DSM, and behavioristic classification. Keywords: Emotional and Behavioral Disorders, Impaired, Children with Special Needs